Bisnis Digital Distributor Alat Rumah Tangga Kue Kering Jan Endols: Implementasi Strategi Manajemen Pendampingan Kewirausahaan di Kota Mojokerto : Penelitian - Umagapi, Dara Anindya Putri; Huda, Achmad Nuril; Hermawan, Agus; Winarno, Agung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The goal of the mentoring program for Mojokerto's Obral Gerabah MSMEs is to strategically build the local economy by focusing on home pottery and plastic crafts. The goal of this curriculum is to assist business owners in developing their digital financial record-keeping, stock management, and marketplace and social media promotion skills. Approach, elicitation, deepening, matching, interpretation, and presentation are the six stages of the participatory implementation technique. The activity's outcomes include a 20% rise in turnover, an improvement in inventory management efficiency, and a rise in business owners' digital knowledge. The competitiveness and sustainability of local enterprises can be greatly impacted by minor measures in mentoring MSMEs, as this program demonstrates.